HDAC inhibitors Panobinostat and Romidepsin enhance tax transcription in HTLV-1-infected cell lines and freshly isolated patients’ T-cells - Schnell, Annika P.; Kohrt, Stephan; Aristodemou, Aris; Taylor, Graham P.; Bangham, Charles R. M.; Thoma-Kress, Andrea K. (Frontiers in Immunology, 2022)
The viral transactivator Tax plays a key role in HTLV-1 reactivation and de novo infection. Previous approaches focused on the histone deacetylase inhibitor (HDACi) Valproate as a latency-reversing agent to boost Tax expression and expose infected cells to the host's immune response. However, following treatment with valproate proviral load decreases in patients with HAM/TSP were only transient. Here, we hypothesize that other compounds, including more potent and selective HDACi, might prove superior to Valproate in manipulating Tax expression. Thus, a panel of HDACi (Vorinostat/ SAHA/ Zolinza, Panobinostat/ LBH589/ Farydak, Belinostat/ PXD101/ Beleodaq, Valproate, Entinostat/ MS-275, Romidepsin/ FK228/ Istodax, and MC1568) was selected and tested for toxicity and potency in enhancing Tax expression. The impact of the compounds was evaluated in different model systems, including transiently transfected T-cells, chronically HTLV-1- infected T-cell lines, and freshly isolated PBMCs from HTLV-1 carriers ex vivo. We identified the pan-HDACi Panobinostat and class I HDACi Romidepsin as particularly potent agents at raising Tax expression. qRT-PCR analysis revealed that these inhibitors considerably boost tax and Tax-target gene transcription. However, despite this significant increase in tax transcription and histone acetylation, protein levels of Tax were only moderately enhanced. In conclusion, these data demonstrate the ability of Panobinostat and Romidepsin to manipulate Tax expression and provide a foundation for further research into eliminating latently infected cells. These findings also contribute to a better understanding of conditions limiting transcription and translation of viral gene products.